Estandarización del manejo y la criopreservación de semen de hembras masculinizadas de trucha arco Iris (Oncorhynchus mykiss) - Betancur L., James J.; Montoya, Andrés F.; Mira, Tatiana; Rojas, Francy A.; Olivera A., Martha (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The demand of monosex female stocks in production of trout has significantly increased during the past years, which has led to develop new technologies to standardize this process. The usage of semen of genetic females submitted to sexual reversion is a good choice. The objective of this research was to develop a methodology to mature in vitro and cryopreserved semen of sex-reversed rainbow trout (Oncorhynchus mykiss) females as strategy to produce lineage 100% Colombian trout female. The semen was directly obtained from the gonads after its surgical extraction of the slaughtered individuals, later it was submitted to maturation process implementing seminal plasma of normal males and artificial plasma. The semen was cryopreserved in two extender dimetyhyl sulfoxide 10% and methanol 10%. Postmaturation, postcriopreservation movility and sperm fertility were evaluated. Maturation process had a significative Maturation process had a significativeeffect on movility, the highest movility was obtained with artificial seminal plasma (55 ± 10.4 %). Highest post criopreservation movility (29.9 ± 13.3%) and highest fertility rates (26.33 ± 7.53 %) were obtained with dimetyhyl sulfoxide 10%.